THE INTERCONNECTION BETWEEN BIOLOGICAL MECHANISMS AND SOCIO-PSYCHOLOGICAL ADAPTATION IN SEVERELY WOUNDED COMBATANTS (Psychology Travelogs, 2025)
The article provides a comprehensive analysis of biological theories of socio-psychological adaptation of severely wounded combatants and their impact on the restoration of psychophysiological functions. It shows that after the start of full-scale war in Ukraine, the issue of effective rehabilitation of veterans and wounded military personnel has become particularly relevant, as it combines medical, psychological, and social dimensions. The essence of biological adaptation mechanisms is revealed, which ensure the body’s ability to restore balance after trauma and form new strategies for functioning.Based on the works of domestic researchers and modern psychophysiological approaches, it has been proven that biological adaptation is the basis for cognitive recovery, emotional regulation, and motivational activity of combatants. It has been substantiated that it is advisable to use a comprehensive approach to the analysis of adaptation mechanisms covering various levels of an individual’s response to traumatic events. A classification of types of personal adaptation in the process of rehabilitation of severely wounded combatants is presented. The use of VR therapy with biosensor integration, neurostimulation, and sensorimotor training as effective means of activating compensatory mechanisms of the brain is described.It is emphasized that biological adaptation is an integrative process that combines physiological, psychological, and social components of recovery, ensuring coordinated interaction between the body’s physical reactions, the emotional state of the individual, and their ability to function effectively in a social environment after experiencing stress or trauma. It creates the basis for the formation of stress resistance, positive self-perception, and reintegration into civilian life. The practical significance of the study lies in the use of the results to improve the psychological assistance system, develop rehabilitation programs, and monitor the psychophysiological indicators of combatants’ adaptation.
Keywords: biological adaptation; combatants; psychophysiological recovery; neuroplasticity; sensorimotor compensation